Impact of Obesity on Perioperative and Clinical Outcomes After Robotic Assisted Radical Prostatectomy - Sahin Kilic; Murat Sambel (Scientific Reports)
Abstract The aim of this study is to evaluate the effect of obesity on robotic-assisted radical prostatectomy (RARP) outcomes. This study included 120 obese patients [body mass index (BMI) ≥ 30 kg/m²] and 124 normal weight (BMI ≤ 25 kg/m²)] patients from a total of 750 patients who underwent RARP between January 2017 and March 2023. The perioperative and long-term oncological and functional outcomes were also analyzed. No significant differences were observed between the groups regarding age, prostate-specific antigen (PSA) levels, or International Society of Urological Pathology (ISUP) grade distribution (p > 0.05). The obese group had significantly longer median surgical times, vesicourethral anastomosis times, hospital stays and drain removal times compared to the control group (p < 0.05). The control group demonstrated significantly better continence recovery rate at the 1st month and erectile dysfunction (ED) recovery rate at the 12th month (p < 0.05). Bilateral nerve sparing (OR: 16.59; p < 0.001) and the preoperative IIEF score (OR: 1.29; p < 0.001) were identified as independent predictors of ED recovery in the multivariable logistic regression model. Bilateral nerve sparing (OR: 3.00; p < 0.001) and the absence of metabolic syndrome (OR: 2.03; p < 0.05) were found to be independent predictors of early continence recovery. There were no differences in systemic progression or overall survival at a median follow-up of 24 months (p > 0.05). While obesity adversely impacts perioperative outcomes, short-term continence recovery rates, and mid-term ED recovery rates, it does not affect mid-term oncological outcomes after RARP.